Salicylate Metabolism in Twins - Daniel E. Furst; Niroo Gupta; Harold E. Paulus (1977)
To evaluate the contribution of genetic influences on the individual variation in plateau serum salicylate levels, salicylate metabolism was studied in seven pairs of identical and six pairs of fraternal twins.